Poetry and English language teaching: How does poem engage EFL young learners in learning English? - Wati, Shafrida; Kurniasy, Dessy (Jurnal Anifa: Studi Gender dan Anak, 2024)
The introduction of English to young learners at an earlier age in foreign language settings has led to recognition of the importance of actively involving pupils in learning the target language. This study aimed to describe the utilization of poetry as an instructional tool to expose English as a foreign language to young learners. It further elaborates how its use could enhance and encourage active participation of the learners during the learning. This qualitative study was conducted at an elementary school in Langsa, a region in Aceh. A total of 25 pupils were purposefully selected as participants in this research. The data were collected through observation and interviews. The findings showed that incorporating poetry effectively stimulates learners’ engagement during the learning process. Students demonstrate enthusiasm and active participation in the classroom activity, as poetry's rhythmic, expressive, and musical elements prevent monotony in their learning experience. Learners demonstrate a favorable disposition towards acquiring English language skills through poetry, as seen by their active engagement in various classroom activities, including generating poetic content, vocalizing poems enthusiastically, and employing non-verbal communication to convey the intended meaning during recitation effectively. They were also exposed to the learning of vocabulary and pronunciation in an engaging way through the poem.